2015
DOI: 10.1177/0969141315604659
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of Bowel Scope (Flexible Sigmoidoscopy) Screening in the English National Programme: the first 14 months

Abstract: Early indications of uptake are encouraging. Future efforts should focus on increasing public awareness of the programme and reducing socioeconomic inequalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
62
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(64 citation statements)
references
References 19 publications
(39 reference statements)
1
62
0
1
Order By: Relevance
“…In contrast to their findings that practical barriers do not play a major role in screening uptake, we found that barriers such as inability to attend the screening appointment do play a role and that these barriers have a greater influence on actual appointment attendance than the initial decision or intention to attend. An analysis of variation in uptake during the first 14 months of the Bowel scope screening programme7 identified that centre effects have an independent association with uptake along with deprivation and gender and that those offered out of hours appointments were more likely to attend screening. Our participants' experiences and satisfaction with re-arranging inconvenient appointment times differed between screening centres.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In contrast to their findings that practical barriers do not play a major role in screening uptake, we found that barriers such as inability to attend the screening appointment do play a role and that these barriers have a greater influence on actual appointment attendance than the initial decision or intention to attend. An analysis of variation in uptake during the first 14 months of the Bowel scope screening programme7 identified that centre effects have an independent association with uptake along with deprivation and gender and that those offered out of hours appointments were more likely to attend screening. Our participants' experiences and satisfaction with re-arranging inconvenient appointment times differed between screening centres.…”
Section: Discussionmentioning
confidence: 99%
“…In the UK, uptake of CRC screening11 23 and more specifically for FS4 7 33 is lower in areas of higher deprivation. Further research is needed to explore the mediating effects of factors associated with higher deprivation such as existing physical and mental health problems (that may affect the desire and/or ability to attend the screening appointment), the lack of desire for potential treatment and lower flexibility in employment leave.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Following this study, screening using flexible sigmoidoscopy was piloted across six centers in England, inviting anyone aged 55 years to undergo screening. The uptake was 43% (45% in men and 42% in women, 33% in low socioeconomic areas)[3]. A Study on patient attitudes towards screening flexible sigmoidoscopy (FS) showed as possible reasons for poor uptake to be embarrassment and concern regarding pain during the procedure[4].…”
Section: Introductionmentioning
confidence: 99%